2019
DOI: 10.1007/s00520-019-04818-w
|View full text |Cite
|
Sign up to set email alerts
|

An immunotherapy survivor population: health-related quality of life and toxicity in patients with metastatic melanoma treated with immune checkpoint inhibitors

Abstract: Purpose The immune checkpoint inhibitors (ICIs) have resulted in subgroups of patients with metastatic melanoma achieving high-quality durable responses. Metastatic melanoma survivors are a new population in the era of cancer survivorship. The aim of this study was to evaluate metastatic melanoma survivors in terms of health-related quality of life (HRQoL), immune-related adverse events (irAEs) and exposure to immunosuppressive agents in a large single centre in the UK. Methods We defined the survivor populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 32 publications
3
36
0
2
Order By: Relevance
“…In a large cohort study (N = 91) comparing IPI survivors with matched controls, Boekhout et al found decreased physical, role, cognitive, and social functioning as well as increased financial difficulties and fatigue symptoms according to the EORTC QLQ-C30 in IPI survivors [38]. These findings are in line with two recently published surveys, both reporting significant ICI toxicity, psychological concerns such as fear of melanoma recurrence, and impairments in specific HRQoL domains (emotional, physical, role, and social functioning) [38,39]. Cognitive function was not assessed with an objective NCF test battery.…”
Section: Journal Of Immunology Researchmentioning
confidence: 60%
“…In a large cohort study (N = 91) comparing IPI survivors with matched controls, Boekhout et al found decreased physical, role, cognitive, and social functioning as well as increased financial difficulties and fatigue symptoms according to the EORTC QLQ-C30 in IPI survivors [38]. These findings are in line with two recently published surveys, both reporting significant ICI toxicity, psychological concerns such as fear of melanoma recurrence, and impairments in specific HRQoL domains (emotional, physical, role, and social functioning) [38,39]. Cognitive function was not assessed with an objective NCF test battery.…”
Section: Journal Of Immunology Researchmentioning
confidence: 60%
“…Two other studies have evaluated patient-reported outcomes of advanced melanoma patients treated with ICI (ipilimumab and/or nivolumab or pembrolizumab). Using a non-cancer-specific measurement, O'Reilly et al [35] found that 73 patients had lower physical, social functioning, and general health levels, compared with an unmatched, normative population after a median follow-up of 25 months. These HRQoL results were established in 30% of patients on various ICI treatments.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of 84 patients with metastatic melanoma who achieved a durable response to an ICI and had been followed for ≥12 months, patients had a statistically significantly lower health related quality of life with regard to physical, social, and physical role functioning and general health compared with population norms. Of these patients, 43% had experienced high grade irAEs and 14% had required treatment with an immunosuppressive agent in addition to corticosteroids 104. For those patients with durable remission from their cancer but left with a new chronic illness, including type 1 diabetes24 or chronic inflammatory arthritis,16 their quality of life is affected in the long term.…”
Section: Patient Reported Health Related Quality Of Lifementioning
confidence: 99%